Challenges and intercultural adaptation among Japanese students to Malaysian culture : a case study - Isma Rosila Ismail; Roswati Abdul Rashid; Rosmalizawati Ab Rashid; Parveen Kaur Sarjeet Singh; Yus Sharmiza Yushriman (Penerbit Universiti Kebangsaan Malaysia, 2022)
Outcomes of a case study based on the Autobiography of Intercultural Encounters (AIE) released by the Council of Europe are presented in this article. The paper is created as a supplement to help students reflect critically on unique intercultural interactions. The study claims that the document may be utilised in its original question-and-answer format to examine intercultural experiences critically and as a framework for students to create intercultural encounter narratives. As a result, this document may be used to write reflective narratives on students’ intercultural experiences, such as studying abroad. Two Japanese students on a short program in Malaysia were asked to create a story on their intercultural experiences for this research. The students then submitted their responses to the same experience’s questions in AIE. They created their narrative using AIE as a framework, and content analysis of the two AIE narratives indicated that the narrative based on AIE was more critical in its perspective of intercultural encounters. According to the findings, the student found creating a story focused on AIE to be helpful to both herself and the audience. Therefore, it can be concluded that adopting AIE as a framework for writing intercultural encounter narratives might be beneficial, particularly in describing intercultural communication scenarios. Students might enhance their awareness of intercultural conflict situations and develop their communication skills by reading such collected narratives.